2008
DOI: 10.1038/jid.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins and Their Receptors Stimulate Melanoma Cell Proliferation and Migration

Abstract: Melanoma is a highly aggressive skin tumor that originates in the epidermis from melanocytes. As melanocytes share with the nervous system a common neuroectodermal origin and express all neurotrophins (NTs), we evaluated the expression and function of NTs and their receptors in melanoma. We report that primary and metastatic melanoma cell lines synthesize and secrete all NTs. Moreover, melanoma cells express the low-affinity (p75NTR) and the high-affinity tyrosine kinase NT receptors (Trk). The inhibition of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 31 publications
(32 reference statements)
4
135
1
1
Order By: Relevance
“…In melanoma cells, it has previously been shown that the addition of proNGF can lead to a stimulation of cell invasion through activation of p75 NTR and sortilin (28); in this model, TrkA was not found to be necessary. However, the activation of TrkA by proNGF has also been reported in other models (8), with the biological activity of proNGF dependent upon relative levels of TrkA versus p75 NTR (29).…”
Section: Discussionmentioning
confidence: 63%
“…In melanoma cells, it has previously been shown that the addition of proNGF can lead to a stimulation of cell invasion through activation of p75 NTR and sortilin (28); in this model, TrkA was not found to be necessary. However, the activation of TrkA by proNGF has also been reported in other models (8), with the biological activity of proNGF dependent upon relative levels of TrkA versus p75 NTR (29).…”
Section: Discussionmentioning
confidence: 63%
“…p75NGFR is a member of the TNFR superfamily and has been shown to be a conditional tumor-suppressor gene (19). In breast cancer and melanoma, p75NGFR acts as an oncogene, increasing cell proliferation, survival, and migration (6,(20)(21)(22). In contrast, in prostate cancer and neuroblastoma, p75NGFR acts as a tumor-suppressor gene, inducing apoptosis and inhibiting cell proliferation and invasion (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of p75NGFR has been observed in several human cancers, such as thyroid carcinoma, stomach cancer, and liver cancer (5)(6)(7)(8)(9)(10). p75NGFR has different functions based on the tumor type in which it is found.…”
Section: Introductionmentioning
confidence: 99%
“…As melanoma could originate from melanocytes and melanocytes seem to benefit from the cutaneous neurotrophic network mainly as paracrine targets, once malignant transformation occurs, melanoma cells acquire self-renewal capabilities mediated also by autocrine NTs loops. Indeed, all NTs, particularly NT-3 and NT-4, have been detected in conditioned medium of different melanoma cell lines (Truzzi et al, 2008). Recent results show that melanoma cells proliferate through autocrine NTs stimulation.…”
Section: Nts and Melanomamentioning
confidence: 99%